The expression of religious elements and factors of religious thoughts in the empress’s ceremonial costume “Hui Yi” of Song Dynasty / Shuhua Zhang ... [et al.]. - Shuhua, Zhang; Shanat, Musdi; Lee Abdullah, Qistina Donna (Universiti Teknologi MARA Cawangan Sarawak, 2021)
Hui Yi (袆衣) is the highest standard ceremonial costume to the empress in the Song Dynasty, used for important occasions such as wedding ceremonies, coronations, holding court, and ancestral shrine sacrifices. This paper uses the method of literature research, as well as using the method of mutual demonstration of historical books and image data to summarize the types of religious elements in the Song Dynasty empress’s Hui Yi (袆衣). By using interdisciplinary research methods, combined with art, sociology and history, this paper analyzes the reasons for the formation of religious elements.